POTENSI SENYAWA ORGANIK TIDAK TER-ION DALAM MENGURANGI KELARUTAN BESI (FE) UNTUK MENINGKATKAN PRODUKTIFITAS TANAH SAWAH BUKAAN BARU - Herviyanti Hariyanti; Asmar Asmar (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2005)
The research about potency of non-ionic organic compounds to decrease the dissolved iron (Fe) and to increase productivity of recently used ricefield had been conducted from August 2004 till January 2005. The objective was to study the effect of non-ionic organic compounds applied to control Fe and to increase rice production on recently used ricefield. The experiment used completely randomized design with four treatments and three replications. The treatments were consisted of four levels of non-ionic organic compounds (polysaccaride), those were 0, 75, 150, and 225 ppm. The result of this study showed that the effect of non ionic-organic compounds (polysacaride) at 225 ppm could reduce solubility of Fe2+ from 302,67 to 126,67 ppm for 30 days flooded. The yield of the rice (dry weight of grain and percentage filled out of grain) increased as much as 2,95 g dan 35 % with effect of polysaccaride at 225 ppm. Key words : non-ionic organic compounds, polysaccaride, recently used ricefield, flooded.